Human middle cerebral artery blood velocity during sexual intercourse - Hayward, W. A; Fritz, K. R; Greene, E. R (Journal of ultrasound in medicine, 2000)
Although the augmentation of central hemodynamics during human sexual intercourse is well established, dynamic changes in human regional cerebral blood flow have not been reported. Noninvasive transcranial Doppler ultrasonography has been well validated and allows direct, continuous measurement of phasic blood velocity in the human middle cerebral artery (a linear index of regional cerebral blood flow). The middle cerebral artery supplies the premotor and primary sensorimotor cortical regions for the arms, upper and lower trunk, and head. Blood velocities in this vessel have been shown to increase significantly with sensory stimuli and physical stresses. Accordingly, we tested the hypothesis that human sexual intercourse increases middle cerebral artery blood velocity. We used noninvasive, transcranial Doppler ultrasonography (95% confidence limits for precision ± 7%) to measure blood velocity in the left middle cerebral artery of 10 male and 10 female, sexually acquainted, healthy adults (age range, 23 to 47 years; mean, 30 years). To eliminate signal artifacts and allow complete freedom of motion, a modified low profile, temporal fossa transducer was secured by minimal unobtrusive forehead strapping. Continuous measurements of phasic blood velocity and heart rate were made in a private bedroom setting during rest (control), preexcitement, excitation, prepenetration, penetration, preorgasm, orgasm, and resolution with the untethered instrumented subject in the supine missionary position. Heart rate and blood velocity responses were similar in both sexes. During orgasm, the maximal heart rate increased significantly (P < 0.05): 49 ± 44% in women, 65 ± 32% in men, and 58 ± 38% combined from a combined resting value of 77 ± 11 standard deviations SD beats per minute. Importantly, blood velocity in the middle cerebral artery of the 20 subjects remained unchanged (P > 0.10) from a resting value of 56 ± 15 cm/s. In conclusion, in both sexes, human middle cerebral artery blood velocity, a linear index of human regional cerebral blood flow, does not increase significantly (P > 0.10) during human sexual intercourse.